Drop in Overinvestment, Marginal value of Cash Holdings, and Governance System of Companies Listed on Tehran Stock Exchange - Vahedi, Adel; Mohammadi, Hamidreza (European Journal of Sustainable Development, 2018)
This study aimed to investigate overinvestment, marginal value of cash holdings, and governance system of companies listed on Tehran Stock Exchange (TSE). For this purpose, 159 companies listed on TSE during five years (2011-2015) in 795 observations were studied and hypotheses were tested using panel data method in EViews. The results showed that there is an inverse and significant relationship between market value of cash holdings level and overinvestment of the company but governance system did not influence the inverse and significant relationship between market value of cash holdings level and overinvestment. Keywords: overinvestment, cash holdings level, governance system